2016
DOI: 10.1007/s00436-016-5197-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, molecular and MALDI-TOF mass spectrometry identification of ixodid tick species collected in Oromia, Ethiopia

Abstract: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) technology has recently been reported as a promising method for arthropods identification. More recently, our laboratory reported the correct identification of tick species via the MALDI-TOF MS protein spectra profiling of legs from fresh specimens. The aim of the present study was to assess the use of MALDI-TOF MS for correct identification of ixodid tick species preserved in 70 % ethanol during field collection in Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 46 publications
5
76
0
Order By: Relevance
“…In the present study, the time between anthelmintic treatment and collection of feces was 24–60 h, during which the worms start to autolyze. The effect of appropriate sampling and storage conditions was previously described and, although preservation in 70% ethanol is frequently used, it can have a negative effect on MALDI‐TOF MS measurements, such as the identification of fewer peaks in comparison to fresh specimens …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the time between anthelmintic treatment and collection of feces was 24–60 h, during which the worms start to autolyze. The effect of appropriate sampling and storage conditions was previously described and, although preservation in 70% ethanol is frequently used, it can have a negative effect on MALDI‐TOF MS measurements, such as the identification of fewer peaks in comparison to fresh specimens …”
Section: Discussionmentioning
confidence: 99%
“…to DB3) with MS spectra from ticks stored in the same condition allowed reliable and correct identification. These results confirmed, as previously described (Kumsa et al ., ), that the preservation of ticks in alcohol is compatible with future analysis by MALDI‐TOF MS, on condition that MS spectra from counterpart species that have been stored and prepared under the same conditions have been included in the reference MS spectra database. Additionally, other studies reported MS profile alterations between fresh and 70% ethanol preserved specimens for long periods (Kaufmann et al ., ; Yssouf et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the storing method and its duration can also impact the reproducibility of the MS spectra, altering the reliability of MALDI-TOF MS for species identification. The principal and most common method currently used for ticks and fleas include freezing, 70% ethanol, or Carnoy's buffer (Engelthaler et al, 1999;Reis et al, 2011;Kumsa et al, 2016). Some authors have observed that unlike frozen preservation, ethanol storage for longer periods of time may be detrimental to the reproducibility of tick or flea MS spectra (Karger et al, 2012;Yssouf et al, 2013aYssouf et al, , 2014bRothen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, none of these MSP dendrograms proposed a classification comparable with those obtained using COI gene sequences for phylogenetic tree construction. The MSP dendrograms are not adapted for phylogenetic analyses as previously reported [50,51].…”
Section: Discussionmentioning
confidence: 99%